THE CONTRIBUTION OF DIGITALIZATION AND INNOVATION TO REGIONAL ECONOMIC CONVERGENCE - Mullabayev Baxtiyarjon Bulturbayevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article explores the contribution of innovation and digitalization to reducing socio-economic disparities and fostering regional economic convergence in Uzbekistan. It emphasizes the significance of innovative mechanisms and digital technologies in narrowing gaps in regional economic potential, promoting sustainable growth, and ensuring more efficient use of labor resources. Digital transformation is examined as a catalyst for a new phase of regional development, improving the effectiveness of state investment programs, and enhancing openness and transparency in local governance. The study also reviews international best practices in addressing regional disparities and evaluates their applicability within the Uzbek context. Furthermore, the paper highlights the role of innovation infrastructure, startup ecosystems, and e-government systems as essential drivers of regional competitiveness. The findings provide a foundation for developing scientifically grounded strategies to mitigate interregional inequalities and strengthen inclusive growth.